2017
DOI: 10.1016/j.apenergy.2017.09.049
|View full text |Cite
|
Sign up to set email alerts
|

The impact of natural gas/hydrogen mixtures on the performance of end-use equipment: Interchangeability analysis for domestic appliances

Abstract: Quantifies changes in performance for domestic appliances upon hydrogen admixture.• Interchangeability analysis using calculated burning velocities and Wobbe Index.• Calculated maximum hydrogen fractions verified by flashback measurements.• Fuel-rich premixed appliances are critical for flashback.• Composition of the gas to which hydrogen is added determines the maximum admixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 22 publications
1
73
0
1
Order By: Relevance
“…For example, [166] found that domestic, commercial and industrial appliances are likely to be suitable for up to a 10% concentration of hydrogen. The authors of [167] revealed that the limits on hydrogen concentration depend on the composition of the natural gas to which the hydrogen is added, distinguishing between fuel-rich premixed appliances and lean premixed appliances, and on the national Wobbe thresholds. The authors of [168] reported that hydrogen up to 30% by volume can be used to improve the lean-burn capability and flame burning velocity of natural gas engines.…”
Section: T31mentioning
confidence: 99%
“…For example, [166] found that domestic, commercial and industrial appliances are likely to be suitable for up to a 10% concentration of hydrogen. The authors of [167] revealed that the limits on hydrogen concentration depend on the composition of the natural gas to which the hydrogen is added, distinguishing between fuel-rich premixed appliances and lean premixed appliances, and on the national Wobbe thresholds. The authors of [168] reported that hydrogen up to 30% by volume can be used to improve the lean-burn capability and flame burning velocity of natural gas engines.…”
Section: T31mentioning
confidence: 99%
“…Thermal The hydrogen addition to natural gas reduces the CO 2 emissions as there is a lower quantity of carbon in the blend to oxidize (see Figure 24). However, since the hydrogen heating value is lower than that of natural gas, the CO 2 emission decrease is non-linear due to the higher amount of fuel required to generate the same heat of combustion [672]. Further, the addition of hydrogen reduces the number of unburned hydrocarbons and CO due to displacement of carbon-containing fuel, and high flammability limits and rapid flame propagation that favor complete combustion [652,673].…”
Section: Combustionmentioning
confidence: 99%
“…13, x FOR PEER REVIEW 52 of Reduction of the CO2 emissions at constant energy input as a function of the mole fraction of H2 and NG (natural gas) and energy fraction delivered by H2. Reprinted with permission from[672].…”
mentioning
confidence: 99%
“…At final consumer locations, when the concentration of hydrogen at natural gas is high, system adjustment may be required as studied by [54]. A review by [55] shows hydrogen must be preserved at a certain fraction to maintain the performance of domestic appliances in the residential and commercial sectors. In the power sector, modern gas turbine power plants can burn over 50% hydrogen by volume in natural gas.…”
Section: Technical Challenges For Injection Into the Natural Gas Networkmentioning
confidence: 99%